2015
DOI: 10.17559/tv-20141216213746
|View full text |Cite
|
Sign up to set email alerts
|

The influence of demographic and organizational factors on knowledge sharing among employees in organizations

Abstract: Original scientific paper This paper analyses various personal and organizational factors that affect knowledge sharing between employees in organizations. Personal factors involve general demographic characteristics i.e. gender, age and years of experience, and also technical, social or natural orientation of the profession of employees. Characteristics of organizations that were examined regarding knowledge sharing behaviour are the type of ownership and production or service activity of the organization. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…With respect to knowledge sharing, in a sample from Central Europe, Grubić-Nešić et al (2015) concluded that gender, education level, and tenure affected knowledge sharing. However, age and years of experience did not have an effect.…”
Section: Organizational Variables: the Demographics Effectmentioning
confidence: 99%
“…With respect to knowledge sharing, in a sample from Central Europe, Grubić-Nešić et al (2015) concluded that gender, education level, and tenure affected knowledge sharing. However, age and years of experience did not have an effect.…”
Section: Organizational Variables: the Demographics Effectmentioning
confidence: 99%
“…Knowledge is an essential commodity that promotes organizational effectiveness and growth. According to Grubić-Nešić, Matić and Mitrović (2014) knowledge can be defined as a combination of experience, contextual information that provides a framework for the evaluation and application of new information and newly acquired experiences. One of the key factor of knowledge management is knowledge sharing.…”
Section: Influence Of Demographic Factors On Knowledge Sharing Among mentioning
confidence: 99%
“…The knowledge created in an organization is the intellectual capital, valuable property of the organization. Therefore, managing this property means retaining the knowledge and updating it by creating new knowledge and storing, sharing, and acquisition of knowledge (Beck 2009;Grubic-Nesic et al, 2014). Having a good relationship is good power of knowledge sharing both in physical and virtual communities (Bock&Kim., 2002;Dholakia, 2005).…”
Section: Knowledge Management Age-diverse Workforce (Kmdw)mentioning
confidence: 99%